Minimizing consistent Academic Staff Union of Universities (ASUU) strike in Nigeria: Implication on adult education programme - K. C., Adindu; V. A., Ifeanacho; B. G., Dorcas (Journal of Research in Adult and Continuing Education, 2023)
The study is on minimizing consistent (ASUU)strike in Nigeria. Implication on Adult Education Programme. ASUU strike is no longer news in Nigeria and a sort of bi-annual occurrence considering the frequency in a decade. The history of ASUU strike actions in Nigeria was identified, including the causes which include poor welfare packages, harsh government policies, hijacking of administrative roles of university system, corruption,platform of payment, autonomy, among others. The consequences and implication on adult educationprogramme included brain drain, prolonged graduation of students, dilapidation of university infrastructure, delayed implementation of Adult education programme and objectives in line with international standards. The paper recommended sustainable financial autonomy for university system, administrative autonomy except salary and recruitment.consistent dialogue with the union before implementing unpopular policies and resolving previous agreement. In conclusion, the paper is of the position that good governance and leadership is the panacea to adjust the lapses in policy implementation that will bring about minimal strikes in the university system.
Keywords: Strike; ASUU; Implication; Adult; Education